Effects of Recurrent Acute Otitis Media on Cortical Speech-Sound Processing in 2-Year Old Children - Haapala S (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Objectives: To investigate at the age of 2 years the effects of childhood
recurrent acute otitis media (RAOM) on central auditory processing by
using cortical event-related potentials elicited by syllable stimuli.
Design: During a 1-year period, 22- to 26-month-old children fulfilling
the criteria for tympanostomy tube insertion in Oulu University Hospital,
Oulu, Finland, were recruited to the RAOM group (N = 20). The control
group (N = 19) was matched by age, sex, and mother’s educational level.
In both groups, children were typically developing and had no family history
of language disorder or developmental language problems. Finnish
syllables /ke:/ and /pi:/ as standards and their variants with changes in
frequency, intensity, vowel, consonant, and vowel duration as deviants
were used to record P1, N2, and mismatch negativity (MMN) responses
in the multifeature paradigm. The clinically healthy ears at the time of
registration were a prerequisite for the participation.
Results: Children with RAOM and their controls showed the age-typical
P1 and N2 responses with no differences in the amplitudes or latencies
between the groups, which suggests unaffected basic encoding of
sound features and sound representation formation. However, the groups
showed different auditory discrimination profiles. In children with RAOM,
frequency and vowel MMN amplitudes were increased. Furthermore, the
MMN latency for the frequency change was shorter and the frequency
MMN amplitude lateralized to the left hemisphere in the RAOM group
instead of an adult-like right-hemispheric lateralization observed in the
controls. The children with RAOM had a more anterior MMN amplitude
scalp distribution for the intensity change than control children. In
addition, the MMN amplitude elicited by consonant change was evenly
distributed unlike in controls, who had a left-side preponderant lateralization.
Taken together, these results suggest an elevated responsiveness
for frequency, vowel, and intensity changes, and an immature pattern of
discriminating small speech sound contrasts in children with RAOM.
Conclusions: The results suggest that childhood RAOM does not affect
the central auditory pathway integrity or sound encoding. However,
RAOM may lead to aberrant preattentive discrimination of sound features
even when the peripheral auditory input is normal. These results
are clinically significant because even transient problems with auditory
processing may delay language development.